Comparative analysis of myocardial deformation in patients recovered from mild SARS-CoV-2 infection - Baltodano-Arellano, Roberto (2021)
Objectives. During acute infection by the SARS-CoV-2 virus, myocardial involvement has been demonstrated; it is unknown if cardiovascular sequelae in patients recovered from this infection and if these are associated with global morbidity and mortality. The objective of this study was to compare myocardial deformation in patients recovered from mild SARS-CoV-2 virus infection with healthy controls. Materials and methods. This was a cross-sectional observational study that included 33 subjects recovered from mild SARS-CoV-2 infection, who were diagnosed in the previous three to six months, and 31 healthy volunteers, both groups free of cardiovascular risk factors. The study of myocardial deformation was performed using echocardiography with the speckle tracking modality. Clinical and anthropometric variables were compared. Results. The 2D global longitudinal strain of the left ventricle was lower in the subjects recovered from mild SARS-CoV-2 infection than the controls (-20.2% ± 2.6 v -21.6% ± 2.4; p: 0.036). Both groups presented differences in the three ventricular levels, significant at the apical level (-21.2 ± 4.0 vs -23.4% ± 4.2; p: 0.044). The effect by levels shows an inverse Takotsubo pattern. The left ventricular ejection fraction was preserved in both groups (p: 0.153). Conclusions. Left ventricular myocardial deformation is affected in subjects recovered from mild SARS-CoV-2 infection, while the ejection fraction was found in normal ranges. Our study shows a potential role of global longitudinal strain in the detection of subclinical myocardial alterations in patients who had SARS-CoV-2.